Examining orthorexia nervosa: Using latent profile analysis to explore potential diagnostic classification and subtypes in a non-clinical sample. (1st February 2023) - Levin, Rivka L.; Mills, Jennifer S.; McComb, Sarah E.; Rawana, Jennine S.
Abstract: Orthorexia nervosa (ON) is a proposed psychological disorder characterized by a pathological preoccupation with healthy eating. The purpose of the current study was to clarify the relationships between ON and related forms of psychopathology. In addition, we sought to explore whether there may be subtypes of ON and if ON is associated with BMI, gender, or social media use. The sample included 333 undergraduate students (72% female, M age  = 20.91) who completed measures of ON, eating disorder (ED) symptoms, obsessive compulsive disorder (OCD), obsessive compulsive personality disorder (OCPD), and health anxiety. Latent profile analysis detected three distinct groups with high ON scores. The ON/ED combined group ( n  = 16) was characterized by high levels of psychopathology, particularly in the areas of ON and eating disorder symptoms. In comparison, the ON/ED combined, without weight/shape concerns group ( n  =  35 ) had fewer body-related concerns. The ON only group ( n  = 23) reported minimal ED pathology. Regression analyses revealed those in the ON only group were more likely to be male, while the ON/ED group was associated with higher BMI. Being in the ON/ED combined, without weight/shape concerns was associated with viewing and sharing healthy eating content on social media. Our findings suggest that ON has the most overlap with ED pathology as compared to OCD, OCPD, and health anxiety, and that there may be three subtypes of ON. The first two share significant overlap with ED symptomatology while the third appears relatively distinct, characterized by less disordered eating and fewer positive emotions related to healthy eating. Future research should examine these subtypes more closely to determine whether they are clinically meaningful, potentially requiring different interventions.